The Effect of Coating on the Durability of Recycled Pine Wood Pallet - Delviawan, Arif; Famitha, Ithya Ayu Wulan; Hazanah, Shafa Tiranita (JURNAL AGRIMENT, 2024)
Recycled pine wood pallets serve as a viable alternative material for diverse construction and furnishing applications. However, its durability requires enhancement to increase resistance to termites, fungi, and other deleterious agents. Coating treatment is one method to enhance the durability of recycled pine wood pallets. Applying a coating to wood can enhance its durability and extend its service life. The application of the coating can impact the effectiveness and durability of recycled wood boards. Consequently, additional research is required to ascertain the impact of coating type on the longevity of utilized pallet pine wood. Five categories of coatings, specifically wood paint, used oil, cooking oil, thinner, and polish, were administered to the wood sample specimens. This research employed the graveyard test method by submerging wood samples (three-quarters of their length) in soil for two months at the Faculty of Agriculture, Brawijaya University, Malang. Six replications were conducted for each treatment. Coating treatment is anticipated to provide an alternative for enhancing the longevity of utilized pallet wood, which frequently lacks enough protection against destructive agents like termites and fungi. The findings indicated that the coating treatment markedly enhanced the durability of utilized pallet pine wood against biological threats and environmental influences. The treatment of cooking oil, in comparison to alternative methods, demonstrated efficacy in mitigating weight loss in wood samples, signifying enhanced protection against termites, fungi, and environmental conditions. In contrast, uncoated wood exhibited considerable damage, signifying its vulnerability to biological and environmental assaults.